Seabed depressions in the Ingøydjupet Trough and their relation to buried canyons on the Loppa High, Barents Sea - Prytz, Richard (UiT The Arctic University of Norway, 2016)
Large seabed depressions in the Ingøydjupet Trough have previously been interpreted to be formed by sub-glacial melt-water. However, fluid migration and gas expulsion occur over large parts of the Barents Sea, which are frequently associated with seabed depressions. This thesis studies how the seabed depressions are related to sub-surface canyons on the southern part of the Loppa High, SW Barents Sea. The canyons are located stratigraphically below the seabed depressions, and high-amplitude zones at the canyon crests indicate accumulation of gas. Migration of fluids seems to take place along the canyon flanks, and the canyons and their infills have been mapped out in order to infer the distribution of shallow gas and their relation to the seabed depressions. Uplift and erosion have influenced the fluid flow system several times since the formation of the canyons. The final phase was related to glacial isostatic adjustment causing the gas to expand and build up pressure before eruption and seepage of shallow gas took place. Severe erosion further caused the seismic unit S2 to the absent in the southwestern parts of the study area. The thickness of S2 appears to affect the distribution of depressions and fluid migration, as it acts as an impermeable barrier where it is present and thus prevents fluids to reach the seabed and form depressions. The large seabed depressions above the canyons occur in areas where S2 is not present, which suggests that shallow gas is indeed a major contributor to the seafloor topography.